Total phenolic, flavonoid and antioxidant activity of 23 edible flowers subjected to in vitro digestion. (August 2015) - Chen, Guan-Lin; Chen, Song-Gen; Xie, Ying-Qing; Chen, Fu; Zhao, Ying-Ying; Luo, Chun-Xia; Gao, Yong-Qing
Highlights: First measurement concerning the flowers' antioxidants following in vitro digestion. New information on the antioxidants of flowers. Multiple methods for the measurement of total antioxidant capacity were highlighted. The relations between DPPH value, FRAP value and TEAC value as well as total phenolic content were studied. Abstract: In order to provide new information on the antioxidant activities before and after in vitro digestion of the selected flowers for consumers, nutritionists, and food policy makers, total phenolic and flavonoid contents and antioxidant capacities of 23 edible flowers were evaluated. In addition, some bioactive components in the flowers were also identified and quantified by ultra performance liquid chromatography (UPLC). The correlations between 2, 2-diphenyl-1-picrylhydrazylradical scavenging activity assay (DPPH), Ferric reducing antioxidant power assay (FRAP), and ABTS + radical cation scavenging activity assay (ABTS) values and total flavonoid contents and total phenolic contents were also evaluated. Three flowers, Osmanthus fragrans (Thunb.) Lour, Paeonia lactiflora Pall, and Rosa rugosa Thunb (purple) showed the strongest antioxidant activities before or after the digestion, which implied that these flowers are important natural sources for the prevention of oxidative stress diseases.